Analysis of Factors Influencing the Use of Extruder for Fish Feed Manufacturing in Benin - Abraham Nougbognon Tossou; Barnabe Koessi Lié Zokpodo; Nodiet Melody Dahou (Journal of Agronomy, Technology and Engineering Management)
Fish feed is a sensitive operation in fish farming, particularly in terms of economics and quality. The aim of this study is to assess the factors affecting fish feed manufacture in Benin and the use of the extrusion process in such manufacture. The survey questioned 385 producers in agricultural development pole 7 about their socio-economic profile and their understanding of the problems encountered in fish feed manufacture. The results showed that fish feed manufacturers accounted for 22.86% of the producers surveyed and the use of pellet extruders accounted for only 1.8% of the total number of fish farmers. The factors “study environment” and “type of feed purchased” determined the choice of fish feed manufacturer. The problems encountered in the manufacturing process are clogging, high energy consumption, buoyancy of the feed produced, and high production costs. For fish farming in Benin, it would be advisable to design a mini-extruder with lower acquisition costs, capable of producing floating pellets in a variety of ranges to meet the needs of small-scale fish farms.